Phaeohyphomycosis breast masquerading as fibroadenoma in a young teenage girl. Issue 10 (19th June 2017) - Gupta, Amita Jain; Singh, Meeta; Yadav, Surekha; Khurana, Nita; Jain, Shyam Lata; Chawla, Rohit; Laka, Sunil; Mishra, Anurag
Abstract : Phaeohyphomycosis is an unusual granulomatous fungal infection, observed in immunocompromised or diabetic patients; however, it is even rarer in immunocompetent patients. Cytological findings of the same have been infrequently reported. The histopathological diagnosis or fungal culture helps in definitive diagnosis to identify the exact fungal species. Hereby, we report a rare case of invasive fungal infection in a breast lump in a young female, presenting as fibroadenoma breast. Fine needle aspiration cytology from the breast lesion showed the presence of septate acute‐angled branching fungal hyphae with focal pigmentation, morphologically suggestive of phaeohyphomycosis which was positive with fungal stains. This was later confirmed on biopsy as histopathology slides showed the presence of prominent pigmented fungal hyphae. The pus culture from needle aspirate also showed phaeohyphomycotic fungal organism delineating the species Exophiala dermatitidis . Aspiration cytology is crucial for the diagnosis of fungal infection in such cases. An appropriate diagnosis will help in early detection and treatment of such infections as these are usually associated with high morbidity and mortality.